2015
DOI: 10.1101/gad.269324.115
|View full text |Cite
|
Sign up to set email alerts
|

GCN2 sustains mTORC1 suppression upon amino acid deprivation by inducing Sestrin2

Abstract: Mammalian cells possess two amino acid-sensing kinases: general control nonderepressible 2 (GCN2) and mechanistic target of rapamycin complex 1 (mTORC1). Their combined effects orchestrate cellular adaptation to amino acid levels, but how their activities are coordinated remains poorly understood. Here, we demonstrate an important link between GCN2 and mTORC1 signaling. Upon deprivation of various amino acids, activated GCN2 up-regulates ATF4 to induce expression of the stress response protein Sestrin2, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(180 citation statements)
references
References 42 publications
9
170
0
1
Order By: Relevance
“…In our current and past in vivo models, we see hyperactivation of mTORC1 within the first 30-60 minutes of amino acid depletion which is sustained for at least 6 h. Based on time course results by ourselves and others, we conclude that ATF4 is not necessary to inhibit mTORC1 in response to amino acid deprivation. Our work also expands on the findings of Ye and colleagues, reporting that GCN2 induces the expression of Sestrin2 to inhibit mTORC1 (16) (20).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our current and past in vivo models, we see hyperactivation of mTORC1 within the first 30-60 minutes of amino acid depletion which is sustained for at least 6 h. Based on time course results by ourselves and others, we conclude that ATF4 is not necessary to inhibit mTORC1 in response to amino acid deprivation. Our work also expands on the findings of Ye and colleagues, reporting that GCN2 induces the expression of Sestrin2 to inhibit mTORC1 (16) (20).…”
Section: Discussionsupporting
confidence: 79%
“…Our lab was the first to identify the existence of coordinated crosstalk between the ISR and mTORC1 pathway in mammals following amino acid deprivation (10). Since then, multiple labs have explored the basis for this bi-directional relationship in tissues and in normal and cancer (8,(13)(14)(15)(16)(17)(18)(19)(20)(21). Despite these efforts, the core factor(s) coordinating ISR-mTORC1 communication during amino acid stress remain mysterious.…”
Section: Introductionmentioning
confidence: 99%
“…This, along with a higher Fgf21, corresponded to an increase in certain transcripts that are known to be increased by activation of the ISR, such as Nupr1 (23,24), Gadd45b (25), Trb3 (26), Asns (25), and Sesn2 (27), thus comprising a liver gene expression signature of the ISR (GES-I) with DPD in vivo ( Figure 6C and Supplemental Figure 6, B and C). Thus, we chose to examine this further and conducted an experiment to test whether activation of the ISR is required for the induction of liver Fgf21 by DPD.…”
Section: Resultsmentioning
confidence: 99%
“…It remains to be seen whether and in what tissues leucine concentrations fluctuate within the relevant range to be sensed by Sestrin2 in vivo, as the levels of interstitial or cytosolic leucine are unknown. Interestingly, another recent study found that Sestrin2 is transcriptionally induced upon prolonged amino acid starvation via the stress-responsive transcription factor ATF4 (Ye et al, 2015), suggesting that Sestrin2 functions as both an acute leucine sensor as well as an indirect mediator of prolonged amino acid starvation.…”
Section: Upstream Of Mtorc1mentioning
confidence: 99%